Patterns of microphytoplankton biomass and diversity in the southern Alboran Sea - IDMOUSSI, HAJAR; HILMI, KARIM; CHARIB, SAID; BAIBAI, TARIK; ETTAHIRI, OMAR; MAKAOUI, AHMED; ARIN, LAURA; ESTRADA, MARTA; LAABIR, MOHAMED; DEMARCQ, HERVÉ; PETERS, FRANCESC; SOMOUE, LAILA; et al. (Mediterranean Marine Science, 2022)
The southern Alboran Sea is a highly dynamic region in the Mediterranean. However, there is few data on microphytoplankton which is, an important component of the marine ecosystem. We, therefore, collected microphytoplankton samples and related the biomass and diversity patterns to ambient variability, considering cross-shore and longitudinal gradients. There was a general eastward decrease in both species richness and biomass, with Cape Three Forks as a transitional point. Diversity increased in coastal areas and decreased with depth. High chlorophyll-a concentrations corresponded to low temperature and low-salinity waters, indicating the Atlantic origin. Microphytoplankton biomass was low in comparison with total chlorophyll, suggesting a dominance of nano- and picophytoplankton. Biomass values increased in the stretch between Cape Three Forks and Al Hoceima Bay, an area highly influenced by upwelled water originating from the northern Alboran Sea. We suggest that the Western Alboran Gyre enhances the development of dinoflagellates while local upwelling enhances the development of diatoms. A statistical relationship was found between microphytoplankton biomass and diversity, especially when diversity was estimated as species richness. These results are crucial for understanding microphytoplankton dynamics and trends in an area that is undergoing climate-derived changes and biodiversity losses.